Financial leasing or renting? Case study in the classroom - María Esperanza Calvo Centeno; Joaquín Galván Vallina; Ma Victoria Gutiérrez Duarte (Financial Internet Quarterly, 2020)
The main objective of the activity is to solve a financial simulation in such a way that the student learns to work in a team through organizational and planning skills, results orientation and responsibility, as it happens in the business world. The methodology used to implement this activity is Flipped Classroom, considering that it is the most appropriate for the students to acquire the skills that allow them to advise the management team of a company. The activity takes place in a consulting project in which a company requests advice from our students to make an investment decision. The company needs to acquire a transport element and wants to know the financial, accounting and tax consequences that could be derived from making the investment through two different financing instruments: financial leasing or renting. The results of the evaluation carried out by the students show significant satisfaction in the acquisition of competences, given that 60% consider that the activity has been highly beneficial in their learning.
Keywords: G3; M4; H2; 330; team teaching; financing; bookkeeping; tax